IMPLEMENTASI PENGGUNAAN MODEL PROGRAMER UNTUK MENINGKATKAN AKTIVITAS DAN KETERAMPILAN KERJA SAMA PADA MUATAN IPAS KELAS V SDN WARINGIN KENCANA - Rahayu, Isnaniah; Aslamiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the low level of student activity and cooperation in social studies, caused by monotonous and lack of variety in learning, low student engagement, and the limited use of learning models and media, which quickly lead to student boredom. One way to address this issue is by implementing the PROGRAMER model in learning. The purpose of this study was to analyze improvements in student activity, cooperation skills, and learning outcomes. This study used Classroom Action Research (CAR) conducted over four meetings. The subjects were 14 fifth-grade students at SDN Waringin Kencana. This study employed both qualitative and quantitative approaches. Data analysis used descriptive qualitative techniques, described in tables, graphs, and percentage interpretations. The results showed an increase in teacher activity from meetings 1 to 4, with a rating of "very good." Student activity from meetings 1 to 4 increased from 43% (less active) to 93% (very active). Student cooperation skills from meeting 4 increased from 50% to 100%. This resulted in an increase in student learning outcomes in the fourth meeting, from 50% to 93%. Based on the results of this study, it can be concluded that the use of the PROGRAMER model can improve student activity, collaboration skills, and learning outcomes. This research is recommended for principals, teachers, and future researchers as an alternative learning model to improve the quality of education.